Gitelman Syndrome: Three Cases of a Rare Genetic Disorder in a Tertiary Care Hospital (Bangladesh Journal of Medicine, 2024)
Gitelman syndrome is a salt-losing tubulopathy caused by mutation of genes encoding sodium chloride (NCCT) and magnesium transporters in the thiazide-sensitive segments of the distal nephron. It is characterized by renal potassium wasting, hypokalemia, metabolic alkalosis, hypocalciuria and hypomagnesemia. Here we present three cases those we encountered in Shaheed Suhrawardy Medical College Hospital.A 20-year-old male who was a soldier of Border Guard Bangladesh presented to us with muscle cramps and tingling & numbness for last 05 days. On examination, we found normotension with positive trousseau’s sign. Investigation revealed hypokalemia with hypomag-nesemia. 24 hours urinary electrolytes were indicating urinary loss. As ABG revealed metabolic alkalosis and urinary calcium creatinine ratio was